The traces of the solutions of the semi-linear equations with fractional derivative with respect to time - Lopushansky, A.O.; Lopushanska, H.P.; Pasichnyk, O.V. (Carpathian Mathematical Publications, 2011)
The sufficient conditions of the existence of the generalized initial values of the regular in domain solutions for semi-linear diffusion equations under perturbations of the fractional derivative with respect to time are obtained.